Kajian Register Bahasa Minangkabau Ragam Adat - Ena Noveria (Fakultas Bahasa dan Seni UNP, 2010)
The aim of this research is to reveal the uniqueness of the cultural style of Minangkabaunese as one of the Minangkabau language diversities. The peculiarities are described in terms of its lexicons and sentence structures. This study was a descriptive qualitative research type. Object of research was the cultural style of Minangkabaunese, while the research data were the customary speech variety. In terms of lexicon, there are a lot of the typical vocabulary items that are rarely or not used in the general variety of Minangkabaunese. The cultural style of Minangkabaunese uses metaphors that are rarely used in the general variety. In terms of sentence structures, this style uses many compound and complex sentences with many subordinate clauses in one sentence. Key words: registered, cultural uniques, Minangkabau, lexicons, structure